Philosophical and Religious Syncretism in the Deus Omnipotens Hymn by Tiberianus (Sincretismo filosofico-religioso e tradizione nell'inno al deus omnipotens di Tiberiano) - Perono Cacciafoco, Francesco (2016)
The current panorama of the studies on the Tiberianus' hymn to the 'deus omnipotens' is still rather limited. This article analyzes - also from the point of view of the language - the Tiberianian text through a so far a little neglected point of view, namely from the perspective of the Author's re-use of philosophical and literary (and religious) stereotypes, aimed at creating an 'imago Dei' filtered through a complementary – even in a mutual exchange between themselves – notions background.